When bad things happen to good people - Kushner, Harold S. (New York, Anchor Books, a division of Random House, Inc., 2004)
Harold Kushner, a Jewish rabbi facing his own child's fatal illness, deftly guides us through the inadequacies of the traditional answers to the problem of evil, then provides a uniquely practical and compassionate answer that has appealed to millions of readers across all religious creeds.
Introduction: Why I wrote this book -- Why do the religious suffer? -- The story of a man named Job -- Sometimes there is no reason -- No exceptions for nice people -- God leaves us room to be human -- God helps those who stop hurting themselves -- God can't do everything, but he can do some important things -- What good, then, is religion?
Keywords: Kushner, Harold S; Theodicy; Suffering; Pastoral counseling (Judaism); Counseling; Life Change Events; Grief; Religion and Psychology; Judaism; Popular Work